PENGARUH PEMBERIAN KUNYIT ASAM TERHADAP DISMENORE PADA REMAJA DI MAJLIS TA’LIM NURUL IKHWAN RT 06/02 KOTA DEPOK - Romlah, Siti Novy; Fadillah, Firdayani; Haryanto, Sri; Rahmi, Junaida; Juniar, Shella (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2021)
ABSTRACT Background : Dysmenorrhea stiffness in the lower abdomen that occurs before or during menstruation, usually dysminorrhea occurs in 2-3 days. The purpose of this study was to determine the effect of giving tamarind turmeric as a dysmenorrhea therapy to reduce pain in young women at M.T Nurul Ikhwan. The design of this study used the Quasy Experiment method with the One group pre-post test design. The total sample size of 23 respondents was obtained by purposive sampling method. The analysis used to determine the effect of giving tamarind turmeric drink on reducing the level of menstrual pain (dysmenorrhea) using the Wilcoxon test. Sign Rank Test. The results of bivariate known Asymp.Sig. (2-tailed) is worth 0.000. Because the value of 0.000 is less than 0.05, it can be concluded that